CONCEPTUAL DESIGN OF BOMB DETECTOR AS ANTICIPATION OF TERRORISM THREAT TO PUBLIC SERVICES - Iris Sumariyanto; Asep Adang Supriyadi; I Nengah Putra A (The Republic of Indonesia Defense University, 2021)
Acts of terrorism are crimes and serious violations of human rights, also the threat of violence that can cause mass casualties and destruction of vital strategic objects. This is an urgent threat that needs to be prepared by designing a bomb detector conceptual design as anticipation of the threat of terrorism in public services. This study aims to obtain operational requirements and conceptual design of bomb detectors as detection of terrorism threats in public services. This study uses a mixed-method with a systems engineering approach and a life cycle model to produce a technological design. The results of operational requirements are sensors, standards, artificial intelligence, integration capability, reliability, calibration mode, portable, and easy to maintain. The configuration design is divided into three stages, namely, 1) sensors including a camera security surveillance system vector image, metal detectors, explosive detectors, and A-jamming; 2) as a processing device, processes an order with the help of an artificial intelligence system; and 3) a security computer (surveillance), early warning, and mobile information to provide information to related agencies, especially the anti-terror unit.